Volume Lalu Lintas Pada Ruas Jalan Di Wilayah Pengembangan (WP) I Kota Pekanbaru - Milanna, Puji Annur; Sasmita, Aryo; Reza, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Development Region I is an area that has the potential to be producer of carbon dioxide (CO2) emissions from transportation activities in Pekanbaru City. This research was conducted to find out the number of motorized vehicles and the value of CO2 emissions produced every day and the value of absorption ability in Development Area I from CO2 emissions transportation activities. The method used is recording traffic activities to calculate the value of number of motorized vehicles. The results of the research, obtained the number of motorized vehicles of CO2 emissions on Development Region I which has 60.333 motorized. Keywords : Carbon Dioxide Emissions,Development Region I